Cancer insights from magnetic resonance spectroscopy of cells and excised tumors. (25th March 2022) - Penet, Marie‐France; Sharma, Raj Kumar; Bharti, Santosh; Mori, Noriko; Artemov, Dmitri; Bhujwalla, Zaver M.
Abstract : Multinuclear ex vivo magnetic resonance spectroscopy (MRS) of cancer cells, xenografts, human cancer tissue, and biofluids is a rapidly expanding field that is providing unique insights into cancer. Starting from the 1970s, the field has continued to evolve as a stand‐alone technology or as a complement to in vivo MRS to characterize the metabolome of cancer cells, cancer‐associated stromal cells, immune cells, tumors, biofluids and, more recently, changes in the metabolome of organs induced by cancers. Here, we review some of the insights into cancer obtained with ex vivo MRS and provide a perspective of future directions. Ex vivo MRS of cells and tumors provides opportunities to understand the role of metabolism in cancer immune surveillance and immunotherapy. With advances in computational capabilities, the integration of artificial intelligence to identify differences in multinuclear spectral patterns, especially in easily accessible biofluids, is providing exciting advances in detection and monitoring response to treatment. Metabolotheranostics to target cancers and to normalize metabolic changes in organs induced by cancers to prevent cancer‐induced morbidity are other areas of future development. Abstract : MRS of cancer cells, xenografts, human cancer tissue, and biofluids is a rapidly expanding field that is providing unique insights into cancer. The purpose of this review is to outline the impact of MRS of extracted cells, tissues, and biofluids, in the discovery, detection, and treatment of cancer, and to provide a perspective on exciting new directions for the future.